(untitled) (The Conference Hub, 2025)
The rapid advancement of mobile technology has led to the frequent replacement of mobile phones, resulting in the accumulation of unused old devices in households. This study explores the potential health and environmental risks associated with keeping these unused mobile phones at home. Utilizing an observational study design, literature review, and expert interviews, we identify significant health hazards such as electromagnetic radiation exposure and chemical leakage from batteries. Additionally, improper disposal of old mobile phones poses serious environmental threats, including soil and water contamination and increased e-waste. Our findings underscore the need for heightened public awareness and improved e-waste management policies to mitigate these risks.